The criteria of language learning website - Hassan, Hanita (2011)
This research attempts to investigate the important elements in language learning websites based on the preference of future English as Second Language (ESL) teachers. Apart from that, other purposes of this study are to investigate the purpose of accessing the websites as well as additional elements that can contribute in improving language learning websites. Subjects are taken from final year undergraduates taking Teaching English as a Second Language as their major. A set of questionnaires was used to collect data and the data were analyzed using quantitative and descriptive analysis. Evaluation was based on frequencies and averages. The findings of this study show that the Internet is one of the most popular sources for learning a language, and websites that introduce language learning are found to be very useful and had been accessed frequently. Users accessed the websites mainly to search for language notes, activities and materials. The elements contributing to the importance of language learning websites are the language of the text as well as users’ control. This study can be used to improve existing language learning websites or to be referred as a guide for future website development.